The Effect of Financial Distress, Profitability, and Leverage on Profit Management with Institutional Ownership as a Moderation in Telecommunications Sector Companies Listed on the IDX - Yazena Putri; Rida Prihatni; Etty Gurendrawari (Politeknik Siber Cerdika Internasional, 2025)
The purpose of this study is to evaluate the influence of financial distress, profitability, and leverage on profit management, as well as to examine the role of institutional ownership as a moderating variable in the relationship between financial distress, profitability, and leverage on profit management. This study uses a quantitative research method. Quantitative research emphasizes more on testing theories through the measurement of research variables with numbers and conducting data analysis with statistical procedures. This study uses a causal design, which is a study that explains the causal relationship of independent variables to dependent variables. The results showed that financial distress, profitability, and leverage had no effect on profit management in telecommunications sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. However, institutional ownership can weaken the influence of financial distress and profitability on profit management, while institutional ownership does not affect the influence of leverage on profit management.